Legal Protection of The Subdivision of Freehold Title Certificates (Shm) as The Basis For Consumer Rights In Sale and Purchase Binding Agreements (PPJB) For Housing Transactions - Era Fortuna Istanlama; Lego Karjoko; Hari Purwadi (International Journal of Science and Environment (IJSE), 2026)
Currently, the demand for residential housing is very high. Therefore, the government permits the transfer of land rights based on a Sale and Purchase Binding Agreement (PPJB), provided that certain requirements are met. One of the requirements is that the agreement must be executed before an authorized Notary, the housing development must have reached at least 20% construction progress, and the developer must have obtained a building permit issued by the relevant government authority. This study aims to examine the legal protection concerning the implementation of the subdivision of Freehold Title Certificates (Hak Milik) as a basis for consumer protection under the Sale and Purchase Binding Agreement (PPJB) in housing transactions. It also analyzes the legal framework governing liability in relation to such legal protection. This research employs a normative legal research method. The legal materials used consist of two types, namely primary and secondary legal materials. The legal materials were collected through library research, while the approaches adopted in this study are the statutory approach and the conceptual case approach. The results of the study indicate that consumers obtain legal protection in a PPJB once they have fully paid the purchase price and the PPJB has been executed before a Notary. Furthermore, if the developer breaches the PPJB, legal protection for consumers may initially be pursued through deliberation to reach a mutual agreement. If no agreement can be reached, consumers may file a lawsuit before the general courts or, alternatively, resolve the dispute through out-of-court mechanisms, which are generally conducted through arbitration.